Volumetric Differences in Four Measuring Systems of Wooden Logs - Chinchilla, Orlando (2005)
The present study shows the differences in volume when using four systems of logs mensuration coming from plantations of Gmelina arborea (melina), Acacia mangium (acacia) y Terminalia ivorensis (terminalia). 416 distributed logs in the following way was evaluated: 294 logs of melina, 97 logs of acacia and 25 logs of terminalia. The diameters oscillated between 11,5 cm and 37,9 cm for the first specie, 17,2 cm and 31,2 cm for the second and 22,3 cm and 48,9 cm for third specie. The volumes obtained in Gmelina arborea were the following: 0,0773 m³ with Smalian, 0,0759 m³ with Huber, 0,0825 m³ with a meter and 0,0539 m³ low with the mensuration system a mecate. In Acacia mangium the following results were obtained: 0,1158 m³ with Smalian, 0,1111 m³ with Huber, 0,1167 m³ with a meter and 0,0739 m³ with a mecate. Terminalia ivorensis registered the following volumes: 0,2564 m³ for Smalian, 0,2474 m³ using the formula of Huber, 0,2387 m³ with a meter and 0,1735 m³ applying the formula a mecate. The species melina and acacia registered the largest volumes under the mensuration system a meter, while in terminalia the largest volume was obtained applying Smalian. The three species registered the smallest volume using the system a mecate.